FOREST PROTECTION EFFORTS AGAINST CONVERTING FOREST FUNCTIONS TO PALM OIL PLANTATIONS - Susanto, Ikbal; Fitriani, Dita; Astika, Hikmah Ayu; Fatimah, Mutiara (Communale Journal, 2023)
The conversion of forest functions to oil palm plantations has often been carried out in Indonesia. Many factors motivate communities, individuals, and companies to do this. One of them is the economic factor. Investment in oil palm plantations is considered a promising investment and generates many profits. However, individuals or companies often need to pay more attention to ecological aspects and the impacts of the forest function's conversion. The consequences resulting from the transformation of forest functions will affect the environment in the short and long term. Forests that have many benefits and uses not only for humans but also for the habitat of animals and plants in them must be protected and preserved. The increasingly widespread conversion of forest functions results from fulfilling human desires and harming other living things, so the government is obliged to make an effort through prevention and mitigation so that the existence of forests and their sustainability are maintained and can continue to bring many benefits to living things.